Masalah-Masalah yang dialami Anak Panti Asuhan dalam Penyesuaian Diri dengan Lingkungan - Rahmah, Silfia; Asmidir, Asmidir; Nurfahanah, Nurfahanah (Konselor, 2014)
Abstract: Teenager who live in orphanage ideally able to make adjustments to the environment. In fact, foster children are often faced with the problem of adaptation to the environment. This research aims to find out what the problem is in the orphan natural adjustment to the environment both in the home environment include peers, caregivers, and outside the home environment includes public and school. This research is descriptive. The research subjects were 24 people at the junior high school level. This research instruments were questionnaires. The result of the research reveal that orphans having trouble adjusting to the orphanage environment include: peer environments, to establish good relationship with peers, and adjustment problems with the caregiver in having the awareness of caregivers authority. Furthermore, the orphanage problems in adjustment to the environment outside the orphanage, include : public around the orphanage is to be sympathetic to the welfare of others, and the problems of adjustment to the school environment is able to make the subject as comfortable as possible. Keywords: Problem, Adaptation, The Ophanage’s Kata Kunci: Masalah, Penyesuaian Diri, Panti Asuhan